2015
DOI: 10.1111/prd.12079
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models for evaluation of periodontal wound healing/regeneration

Abstract: Periodontal wound healing and regeneration are highly complex processes, involving cells, matrices, molecules and genes that must be properly choreographed and orchestrated. As we attempt to understand and influence these clinical entities, we need experimental models to mimic the various aspects of human wound healing and regeneration. In vivo animal models that simulate clinical situations of humans can be costly and cumbersome. In vitro models have been devised to dissect wound healing/regeneration processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 134 publications
(144 reference statements)
0
28
0
Order By: Relevance
“…It is essential that DPSCs will move to the site of new skeletogenesis or during MSC-mediated tissue repair. Many migration assays are available tools for oral regeneration studies [ 44 ]. PL was also already described as efficient in promoting in vitro wound healing of dermal fibroblast [ 45 ], C2C12 mouse myoblasts [ 46 ], keratinocytes [ 47 ], and other human cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that DPSCs will move to the site of new skeletogenesis or during MSC-mediated tissue repair. Many migration assays are available tools for oral regeneration studies [ 44 ]. PL was also already described as efficient in promoting in vitro wound healing of dermal fibroblast [ 45 ], C2C12 mouse myoblasts [ 46 ], keratinocytes [ 47 ], and other human cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical reports have suggested that enamel matrix proteins lead to improved early soft tissue wound healing 7 8 . Based on these clinical observations, it has been suggested that EMD may have an effect on gingival fibroblasts; relevant cells in soft tissue wound healing 9 . The gingival connective tissue is the oral equivalent to the dermis of the skin, and the main residing fibroblast is the gingival fibroblast 10 .…”
mentioning
confidence: 99%
“…(25) Techniques applied in periodontal regeneration therapy include the use of tissue barriers (membranes) and bone and/or bone substitute graft materials such as autografts, allografts, xenografts and alloplasts. (26) Periodontal regeneration still in challenges due to the unique and complex tissue structures. A new era in periodontal management using combined biological mediators to stimulate the processes required for the regeneration of periodontal tissues.…”
Section: Discussion:-mentioning
confidence: 99%